Endometrial microbiome during early pregnancy among women with and without chronic endometritis: a pilot study - Hong Gao; Hong Gao; Na Lu; Yahui Chen; Genlin Li; Huanhuan Li; Innie Chen; Innie Chen; Innie Chen; Amanda Black; Jenna Gale; Jenna Gale; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionAlthough chronic endometritis (CE) is strongly associated with infertility and adverse pregnancy outcomes, the specific microbiome of women with CE who can conceive remain unclear.MethodsThis study recruited 100 participants aged 18 to 45 years with spontaneously conceived pregnancy who opted for pregnancy termination, detected their endometrial microbiome by 16S rRNA, and made a diagnosis of CE.ResultsAmong them, 19 were diagnosed with CE. There was a comparable microbial composition within the endometrium between women with and without CE. The relative abundance of Sphingomonas (21%) and Pseudomonas (8%) were the same in both groups. Compared to women without CE, women with CE exhibited higher abundance of Faecalibacterium (6.5% vs 3.8%), Escherichia-Shigella (3.3% vs 2.6%), Akkermansia (1.65% vs 1.1%), and lower abundance of Lactobacillus (10% vs 14%), and Corynebacterium (1.35% vs 2.15%) at the genus level. Streptococcus, Escherichia-Shigella, Akkermansia and Finegoldia exhibited significant interactions with other microbiome in participants with CE.DiscussionIn women with CE, reproductive potential may be associated with the compositional stability of the endometrial microbiome, whereas an imbalance in the abundance of these microbes may be linked to their pregnancy outcomes.